Strategies and methods to improve compliance in special patient groups and with specific health problems - Turabian, Jose Luis (Archives of Community Medicine and Public Health, 2020)
Adherence to long-term treatments for chronic conditions remains a challenging issue in general medicine. A low proportion of patients follow the recommendations from general practitioners. The attention of all recurrent or chronic health problems and turning points of natural or physiological situations but that present medical health risks requires co-operation with patients and changes in behavior. Taking into account the complexity of the phenomenon of therapeutic compliance, it is necessary to individualize the strategies of approach in general medicine. Some strategies and methods to increase compliance are: 1. Rapport and continuity of care; 2. Confidentiality; 3. Prevention of effects of adverse drug reactions on compliance; 4. Simplify the therapeutic regimen; 5. Self-monitoring; 6. Avoid giving the impression that the drug replaces the need for changes in habits; 7. Know the patient’s agenda, the perceptions of the disease, and the importance and their confidence about adherence; 8. Involve the patient in the decision; and 9. Motivational interview and negotiation. Emphasis should be placed on the importance of doctor-patient relationship and continuity of care, as well as knowing the patient’s agenda, but other strategies are presented according to specific groups of patients and diseases and risk factors, as: 1) Cardiovascular risk factors and coronary heart disease; 2) Hypertension; 3) Hyperlipidemia; 4) Diabetes mellitus; 5) HIV; 6) Osteomuscular diseases; 7) Contraception; 8) Gastroenterological diseases; 9) Psychiatric diseases; 10) Bronchial asthma and chronic obstructive pulmonary disease; 11) Kidney diseases; 12) Elders; 13) Teenagers; and 14) Disabled people. Multiple strategies are probably necessary in most cases.